Physical characteristics of a clayey Yellow Latosol (typic acrorthox) in the state of Amazonas, under different tillage system - Corrêa, José Carlos (Pesquisa Agropecuaria Brasileira, 2014)
The effects of three tillage methods (conventional, notill and rototill) on soil permeability and porosity were evaluated on a clayey Yellow Latosol (Typic Acrorthox) located at EMBRAPA/ UEPAE of Manaus. Tillage treatments caused a significant reduction in topsoil (0 cm - 20 cm) macro porosity when compared to a virgin primary forest site. Consequently values for hydraulic conductivity and basic infiltration on these treatments also changed. The notill treatment presented the largest reductions in permeability suggesting a possible compaction of the topsoil.